Oxidative Stress in Arterial Hypertension (HTN): The Nuclear Factor Erythroid Factor 2-Related Factor 2 (Nrf2) Pathway, Implications and Future Perspectives - Daniela Maria Tanase; Alina Georgiana Apostol; Claudia Florida Costea; Claudia Cristina Tarniceriu; Ionut Tudorancea; Minela Aida Maranduca; Mariana Floria; Ionela Lacramioara Serban (Pharmaceutics, 2022)
Arterial hypertension (HTN) is one of the most prevalent entities globally, characterized by increased incidence and heterogeneous pathophysiology. Among possible etiologies, oxidative stress (OS) is currently extensively studied, with emerging evidence showing its involvement in endothelial dysfunction and in different cardiovascular diseases (CVD) such as HTN, as well as its potential as a therapeutic target. While there is a clear physiological equilibrium between reactive oxygen species (ROS) and antioxidants essential for many cellular functions, excessive levels of ROS lead to vascular cell impairment with decreased nitric oxide (NO) availability and vasoconstriction, which promotes HTN. On the other hand, transcription factors such as nuclear factor erythroid factor 2-related factor 2 (Nrf2) mediate antioxidant response pathways and maintain cellular reduction–oxidation homeostasis, exerting protective effects. In this review, we describe the relationship between OS and hypertension-induced endothelial dysfunction and the involvement and therapeutic potential of Nrf2 in HTN.